2019
DOI: 10.1016/j.jtcme.2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anti-urolithiatic potential of ethyl acetate extract of Pedalium murex L. on struvite crystal (kidney stone)

Abstract: Pedalium murex (L.) is a traditional herb, commonly used for the treatment of kidney stone related problems. Struvite stone can swiftly grow and become ‘staghorn calculi’ in kidney and its associated areas, which is the most aching urological disorder. The present study investigated the anti-urolithiasis activities of ethyl acetate extract of P. murex L. (EAEP) against struvite crystal. The antibacterial activity of EAEP examined against several urease producing bacteria. It showed the minimum bactericidal con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 33 publications
5
11
0
Order By: Relevance
“…In our study the pain, quality of life and total IPSS were improved more in the intervention versus the placebo group. [12][13][14][15][16] Our study is the first research in the literature, which determines the efficacy of cystone in double-J-induced lower urinary tract symptoms. Moreover, the results of this study demonstrated that despite the painful status of double-J stent insertion, the voiding and storage symptoms were improved by cystone or tamsulosin or their combination, leading to better improvement in the total IPSS and VAS.…”
Section: Discussionmentioning
confidence: 99%
“…In our study the pain, quality of life and total IPSS were improved more in the intervention versus the placebo group. [12][13][14][15][16] Our study is the first research in the literature, which determines the efficacy of cystone in double-J-induced lower urinary tract symptoms. Moreover, the results of this study demonstrated that despite the painful status of double-J stent insertion, the voiding and storage symptoms were improved by cystone or tamsulosin or their combination, leading to better improvement in the total IPSS and VAS.…”
Section: Discussionmentioning
confidence: 99%
“…Urolithiasis is defined as the formation of stones within the urinary tract (Kaleeswaran et al, 2018). It is a wellknown disorder that results from integrated biochemical, epidemiological and genetic risk factors (Makasana et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Several factors have increased the prevalence of urolithiasis: Low-intake of vegetables, fruits and fluids, and high consumption of animal proteins, salt and sweetened beverages contribute significantly in prevalence of the urolithiasis (Yachi et al, 2018). Urinary stone formation happens in roughly 12% of the populace with a repeat rate of 70-80% in man and 47-60% in females (Kaleeswaran et al, 2018). It can likewise forever harm the kidneys, if not treated appropriately (Chandrajith et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It may be the oldest crop still grown today. As early as 200-300 BC, it even reached Asian countries 7 . A herbaceous plant called Musa paradisiaca (Musaceae) has a maximum length of 9 m. It has a sturdy, pseudo-treelike stem and a crown of enormous, long, oval, deep-green leaves that can reach lengths of up to 365 cm and widths of 61 cm and large, successively opening ovate bracts, 15-20 cm long, concave, dark red and somewhat fleshy.…”
Section: Introductionmentioning
confidence: 99%